PURIFICATION AND CHARACTERIZATION OF AMYLASE EXTRACTED FROM LOCAL WHEAT PLANT - Sahar I. H., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to test four types of different plants for the purpose of selecting the optimal plant as a source of the amylase enzyme, including wheat, barley, rice, and potatoes. Among these plants, wheat was selected as the best plant source for enzyme extraction because it possessed the highest effectiveness of the enzyme specific activity (3.0 U/mg protein). Furthermore, sodium acetate buffer (0.2 M, pH 6.0) was determined to be the optimal extraction buffer with a 1:5 (w:v) ratio after 75 min, and it provided 68 U/mg protein. The enzyme was concentrated with sucrose before being purified by gel filtration chromatography using Sephadex G-150. The results demonstrated a 1.8-fold increases in final purification folds with a 332% yield of enzymes. At pH 6.0, the purified enzyme showed its highest activity and stability. The activity of the purified enzyme was most effective at 45 °C and remained stable up to 37 °C. At concentrations of 5 and 10 M, various ionic and chemical substances had an impact on amylase.